2023
DOI: 10.1039/d2ma00590e
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic microfluidics for colloidal materials and interface engineering

Abstract: The advent of microfluidic and microfabrication technologies provides vast opportunities for the rational design of colloidal materials and interfaces. However, the development of microscale lab-on-a-chip solutions is greatly limited by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Of course, there are still key bottlenecks in this technology that need to be solved. As a subdivision derived from microfluidic technology, most of the reported proof-of-concept devices were still fabricated with microfabrication techniques, such as photolithography and molding and replicas [193]. After plasma bonding piezoelectric wafers with PDMS material, researchers can customize acoustofluidic devices in a cleanroom in a fast manner.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there are still key bottlenecks in this technology that need to be solved. As a subdivision derived from microfluidic technology, most of the reported proof-of-concept devices were still fabricated with microfabrication techniques, such as photolithography and molding and replicas [193]. After plasma bonding piezoelectric wafers with PDMS material, researchers can customize acoustofluidic devices in a cleanroom in a fast manner.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of acoustic microfluidic reactors include rapid mixing, fine-tuned control over the mixing process, and the capacity to handle sensitive biological materials. [97][98][99] A few studies reported that active microfluidic reactors assisted by acoustic energy were used to synthesize nanoparticles for biomedical applications. 62,[100][101][102][103][104][105] Le et al developed an acoustically actuated microfluidic reactor, providing high mixing efficiency and a high flow rate.…”
Section: Acoustic-assisted Microfluidic Reactor Approach To Develop N...mentioning
confidence: 99%
“…This insulating material is well-known in the field of integrated optics due to its interesting electro-optical, non-linear optical, piezoelectric, and photorefractive properties, which have been successfully combined with microfluidic devices. [18][19][20][21][22][23][24] The high chemical resistance and biocompatibility [25] of LN, together with its high optical transmission in the range 350-3500 nm and its easy interfaceability with polymers and glasses, represent an added value and qualify this material as an optimal choice for biological, and medical applications. In particular, in the case of LN, the photovoltaic properties can be tuned and significantly enhanced by local doping the material.…”
Section: Introductionmentioning
confidence: 99%